Cangkang Siput Sebagai Ide dalam Penciptaan Karya Digital Painting - Astuti Puji Lestari; Ferdian Ondira Asa (Universitas Palangka Raya, 2026)
This final work is a digital painting work that raises the concept of a shell as a metaphor for a house where a house is not only a physical structure but also something built within oneself. Like a shell that a snail always carries, the shell becomes a house as a form of protection so that the snail will feel safe wherever it is. By making a snail shell as a metaphor for a house, it can remind how important the figure of the house is in this digital painting work. The creation of this work follows the method proposed in the art consortium which consists of five stages of creation. These stages include preparation, elaboration, synthesis, realization of the concept, and completion. From all these stages, 10 digital painting works were produced which were then printed, including those with the titles: